Congenital neck masses: embryological and anatomical perspectives - Rasool, Zahida; Hassan, Ashfaq U. (International Journal of Research in Medical Sciences, 2017)
Neck masses are a common problem in paediatric age group. They tend to occur frequently and pose a diagnostic dilemma to the ENT surgeons. Although the midline and lateral neck masses differ considerably in their texture and presentation but the embryological perspective of these masses is not mostly understood along with the fundamental anatomical knowledge. The article tries to correlate the embryological, anatomical and clinical perspectives for the same.